Sled race mystery - Barbo, Maria S.; Del Sur, Duendes (New York : Scholastic, 2002)
Scooby-Doo helps a girl who lost her sled dog. The dog was tired when Scooby-Doo found the dog so Scooby-Doo subsituted for the dog and he won the race.
"24 flash cards inside!"--Cover.
"Preschool-Grade 1"--P. [4] of cover.
Keywords: Winter festivals -- Juvenile fiction; Scooby-Doo (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Sled dogs -- Juvenile fiction; Detective and mystery stories; Detective fiction; Mystery fiction